Morphometric analysis of collagen and inflammatory cells in periodontal disease - Golijanin, Ranko; Kujundžić, Bojan; Milosavljević, Zoran; Milovanović, Dragan R; Andjelković, Zlatibor; Obrenović, Miroslav; Nikolić, Radivoje (Vojnosanitetski pregled, 2015)
Background/Aim. Periodontal disease affects gingival tissue and supporting apparatus of the teeth leading to its decay. The aim of this study was to highlight and precisely determine histological changes in the gum tissue. Methods. Gingival biopsy samples from 53 healthy and parodontopathy-affected patients were used. Clinical staging of the disease was performed. Tissue specimens were fixed and routinely processed. Sections, 5 μm thin, were stained with hematoxylin and eosin, histochemical Van-Gieson for the collagen content, Spicer method for mast-cells and immunochemical method with anti-CD68 and anti-CD38 for the labelling of the macrophages and plasma-cells. Morphometric analysis was performed by a M42 test system. Results. While the disease advanced, collagen and fibroblast volume density decreased almost twice in the severe cases compared to the control ones, but a significant variation was observed within the investigated groups. The mast-cell number increased nearly two times, while the macrophage content was up to three times higher in severe parodontopathy than in healthy gingival tissue. However, the relative proportion of these cells stayed around 6% in all cases. Plasma-cells had the most prominent increase in the number (over 8 times) compared to the control, but again, a variation within investigated groups was very high. Conclusion. Gingival tissue destruction caused by inflammatory process leads to significant changes in collagen density and population of resident connective tissue cells. Although inflammatory cells dominated with the disease advancing, a high variation within the same investigated groups suggests fluctuation of the pathological process.
Keywords: peridontal diseases; gingiva; histological techniques; collagen; macrophages; plasma cells